# Sum of series $\sum \limits_{k=1}^{\infty}\frac{\sin^3 3^k}{3^k}$

Calculate the following sum: $$\sum \limits_{k=1}^{\infty}\dfrac{\sin^3 3^k}{3^k}$$

Unfortunately I have no idea how to handle with this problem.

Could anyone show it solution?

• You probably have a reason to hope this can be done in closed form (perhaps it was a contest problem, for example). Otherise, I would never think it could be done. What, may I ask, is your reason for optimism? Commented Jan 23, 2017 at 7:20
• I am not sure is it a contest problem or not, but i found in one of the papers of problem-solving seminars of my university.
– RFZ
Commented Jan 23, 2017 at 7:24
• @FelixMarin I believe I've warned you not to run amok introducing personal stylistic quirks to other people's posts. \frac is the proper way to write fractions, not \over. Question marks are not to be preceded with a space in English, and it's downright ridiculous to add a period afterwards. Commented Jan 25, 2017 at 3:31
• @RFZ: You didn't sign the right answer (until now) ? Commented Sep 21, 2017 at 7:42
• @Khosrotash, You want likes? :) Oh man this sounds awful :)
– RFZ
Commented Sep 21, 2017 at 10:40

Using $$\sin(3a)=3\sin a-4\sin^3a \to \color{red}{\sin^3(a)=\frac14\Big(3\sin a-\sin(3a)\Big)}$$

so \begin{eqnarray} \sum_{k=1}^{\infty}\frac{\sin^3(3^k)}{3^k} &=& \frac14\sum_{k=1}^{\infty}\frac{3\sin(3^k)-\sin(3.3^k)}{3^k}\\ &=& \frac14\sum_{k=1}^{\infty}\frac{\sin(3^k)}{3^{k-1}}-\frac{\sin(3^{k+1})}{3^{k}}\\ &=& \frac14\sum_{k=1}^{\infty}f(k)-f(k+1)\\ &=&\frac14\Big(\frac{\sin3}{3^{1-1}}-\lim_{n \to \infty}\frac{\sin(3^{n+1})}{3^n}\Big)\\ &=&\frac{\sin(3)}{4} \end{eqnarray}

• Pov: You unlocked god level. (+1) Commented Sep 17, 2021 at 18:30
• @LaxmiNarayanBhandari: thank you a ton. Commented Oct 1, 2021 at 7:49
• I wonder why your answer didn't get accepted. It is literally the best way to do it. Commented Oct 1, 2021 at 11:57

An overkill. Let $\mathfrak{M}\left(*,s\right)$ the Mellin transform. Using the identity $$\mathfrak{M}\left(\underset{k\geq1}{\sum}\lambda_{k}g\left(\mu_{k}x\right),\, s\right)=\underset{k\geq1}{\sum}\frac{\lambda_{k}}{\mu_{k}^{s}}\mathfrak{M}\left(g\left(x\right),s\right)$$ we have $$\mathfrak{M}\left(\underset{k\geq1}{\sum}\frac{\sin^{3}\left(3^{k}x\right)}{3^{k}},\, s\right)=\underset{k\geq1}{\sum}\left(\frac{1}{3^{s+1}}\right)^{k}\mathfrak{M}\left(\sin^{3}\left(x\right),s\right)$$ and since $$\mathfrak{M}\left(\sin^{3}\left(x\right),s\right)=\frac{\Gamma\left(s\right)\sin\left(\frac{\pi}{2}s\right)}{4}\left(3-\frac{1}{3^{s}}\right)$$ we have for $\textrm{Re}\left(s\right)>-1$ $$\mathfrak{M}\left(\underset{k\geq1}{\sum}\frac{\sin^{3}\left(3^{k}x\right)}{3^{k}},\, s\right)=\frac{\Gamma\left(s\right)\sin\left(\frac{\pi}{2}s\right)}{4}\left(3-\frac{1}{3^{s}}\right)\frac{1}{3^{s+1}-1}=\frac{\Gamma\left(s\right)\sin\left(\frac{\pi}{2}s\right)3^{-s}}{4}$$ and so inverting we get $$\underset{k\geq1}{\sum}\frac{\sin^{3}\left(3^{k}x\right)}{3^{k}}=\frac{1}{2\pi i}\int_{1/2-i\infty}^{1/2+i\infty}\frac{\Gamma\left(s\right)\sin\left(\frac{\pi}{2}s\right)3^{-s}}{4}x^{-s}ds$$ now taking $x=1$ and shifting the complex line to the left we have, from the residue theorem, that we have to evaluate the residues of $$\textrm{Res}_{s=-2n-1} \frac{\Gamma\left(s\right)\sin\left(\frac{\pi}{2}s\right)3^{-s}}{4}=\frac{\left(-1\right)^{k}}{4\left(2k+1\right)!3^{-2n-1}}$$ hence $$\sum_{k\geq1}\frac{\sin^{3}\left(3^{k}\right)}{3^{k}}=\frac{1}{4}\sum_{k\geq 0}\frac{\left(-1\right)^{k}}{\left(2k+1\right)!}3^{2k+1}=\color{red}{\frac{\sin\left(3\right)}{4}}.$$

• badass $(+1)$ Commented Jan 23, 2017 at 13:09

We can use the following identity (leaving for you to prove)

$$\sin^3 (3^x) = \frac {1}{4} ( 3 \sin(3^x) - \sin (3^{x+1}) )$$

That is,

$$\frac {\sin^3( 3) }{3} = \frac {1}{4} ( \sin (3) - \frac {1}{3} \sin (3^2) )$$ $$\frac {\sin^3( 3^2) }{3^2} = \frac {1}{4} (\frac {1}{3} \sin (3^2) - \frac {1}{3^2} \sin (3^3) )$$ $$\frac {\sin^3( 3^3) }{3^3} = \frac {1}{4} (\frac {1}{3^3} \sin (3^3) - \frac {1}{3^4} \sin (3^4) )$$ As you can clearly see, all the middle terms cancel out in the sum and we are only left with the first term. So the sum is $$\frac {\sin (3)} {4}$$.

• +1 Pretty fine. The obvious way. Commented Sep 11, 2018 at 20:33